Adaptasi Kinerja Bangunan Rumah Tinggal dengan Ventilasi Atap Responsif - Mufidah Mufidah; LMF. Purwanto; Ridwan Sanjaya (RUAS, 2021)
Thermal comfort is a condition where occupants can feel comfortable doing activities in the building. One of the ways to get comfort is done by passive design, in which the building is designed to adapt weather change outside the building. Because the weather outside is always changing, the planned building design must be responsive to these weather changes. This study uses a responsive roof ventilation model, that the movement of the roof vent covering grille, which serves as an attempt to regulate the exit of wind from the inlet. This study method begins with a literature review on the thermal comfort of residential building in the humid tropics,  as a study of the application of passive design principles as building adaptation to weather changes. Furthermore, an analysis of the ventilation area is made based on the need for thermal comfort in the building. Finally, the planning of building performance systems automatically using the Arduino temperature and humidity sensors. The result is the concept of a framework as applying automation to responsive roof ventilation. This preliminary study is still basic and it is hoped that can be continued in research with the application and experimentation of the roofs in small building